The Curious Case of the Blasphemer Ambiguity as Literary Device in Leviticus 24:10-23 - Fuad, Chelcent (2019)
This article argues that, instead of the nature of the crime or its punishment, the underlying problem that needs oracular law in the account of the blasphemer in Lev 24:10-23 is the ambiguity of the criminal's identity. This ambiguity is employed in the narrative as a literary device by which the redactor of the narrative introduces the universal applicability of the blasphemy law that includes both natives and foreigners. By so doing, the redactor of Lev 24 serves the Holiness Code's theological agenda, namely, the extension of holiness to all inhabitants of the land since pollution of the land by any of its inhabitants may eventually cause the expulsion of the whole people from the land. To this end, the redactor rewrites the Covenant Code and frames it with the narrative of the mixed-pedigree blasphemer.
Keywords: Bibel; Covenant Code; Holiness Code; Ambiguity; Blasphemy; Foreigner; native; talion law